The Influence of School Infrastructure and Principal Managerial Ability on The Performance of Public Elementary School Teachers in Sembawa District - Doni Oktareza; Bukman Lian; Dessy Wardiah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
The purpose of this study was to determine and analyze the influence of school infrastructure and principal managerial skills together on the performance of public elementary school teachers in Sembawa District. This study was conducted comprehensively at public elementary schools in Sembawa District with a total of 25 schools. The research method used in this study is a quantitative descriptive method. The population of this study consisted of all public elementary school teachers in Sembawa District, totaling 271 teachers. Based on the results of calculations using the Slovin formula, the sample obtained was 162 public elementary school teachers in Sembawa District. Data collection techniques used questionnaires, observation and documentation. Data analysis techniques used normality tests, linearity tests, multicollinearity tests, simple correlation analysis, multiple correlation analysis, simple regression analysis, t-tests and F-tests. The results of this study are that there is a significant influence of school infrastructure and principal managerial skills on the performance of public elementary school teachers in Sembawa District with an influence contribution of 29.6%.